Developmental delay and autism with hypertrichosis cubiti: a clue to the diagnosis of Wiedemann-Steiner syndrome - Nerakh, Gayatri; Varma, Chaitanya (International Journal of Contemporary Pediatrics, 2024)
Wiedemann-Steiner syndrome (WSS) is a rare disorder with dysmorphic features, developmental delay, autism, and hypertrichosis. We report a case of a seven and half year-old female child born to a non-consanguineous couple with developmental delay, autism, behavioral abnormality and hypertrichosis cubiti diagnosed to have KMT2A gene associated WSS. It is important for the treating clinician to be aware of the characteristic signs and symptoms of the disorder and the necessity of genetic testing to be able to confirm the diagnosis and manage by multidisciplinary team in any child with developmental delay and autism.